2021
DOI: 10.3390/antibiotics10040415
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Antibiotic Resistance in Important Gram-Positive and Gram-Negative Pathogens and Novel Antibiotic Solutions

Abstract: Multidrug-resistant bacteria have on overwhelming impact on human health, as they cause over 670,000 infections and 33,000 deaths annually in the European Union alone. Of these, the vast majority of infections and deaths are caused by only a handful of species—multi-drug resistant Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Enterococcus spp., Acinetobacter spp. and Klebsiella pneumoniae. These pathogens employ a multitude of antibiotic resistance mechanisms, such as the production of antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 122 publications
(180 reference statements)
0
90
0
Order By: Relevance
“…Intrinsic include influx pumps, as well as several β-lactamases. Specifically, P. aeruginosa has chromosomally encoded AmpC β-lactamases and extended-spectrum-β-lactamases (ESBLs) [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsic include influx pumps, as well as several β-lactamases. Specifically, P. aeruginosa has chromosomally encoded AmpC β-lactamases and extended-spectrum-β-lactamases (ESBLs) [22].…”
Section: Resultsmentioning
confidence: 99%
“…Acquired β-lactam resistance mechanisms in P. aeruginosa include mutations in porins, such as deficiency of the OprD porin, which leads to high-level resistance to imipenem and other carbapenems; overexpression of hydrolyzing enzymes such as AmpC; over-expression of efflux pumps such as MexCD-OprJ, which reduces susceptibility to carbapenems; modification of PBPs, which reduces susceptibility to several β-lactams; and finally, acquisition of other β-lactamases, such as Class B carbapenemases [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…The most dangerous are biofilms composed of pathogenic bacteria E. faecalis , S. aureus , Staphylococcus epidermidis, E. coli , Klebsiella pneumoniae , and P. aeruginosa [ 358 ], which are mostly responsible for hospital infections that are difficult to cure and are characterized by increased resistance to therapies [ 359 ]. The antibiotic resistance of biophimes is the result of, among other things, the presence of a matrix that is a barrier to drug penetration and the production of enzymes responsible for the hydrolysis of ß-lactam antibiotics [ 360 , 361 ]. Research on the potential of nanoparticles to combat biofilms meets the expectations of modern medicine.…”
Section: Synthesis Of Nanoparticles (Nps) By Natural Extractsmentioning
confidence: 99%
“…UTIs may be resolved spontaneously or treated with antibiotics [ 25 ]. Antibiotic resistance is a major problem nowadays [ 26 ]; in the European Union alone, it has been reported that annually, there are around 670,000 cases of infections related to multi-drug-resistant bacteria with 37,000 associated deaths, representing an enormous socioeconomic burden [ 27 ]. Regular use of antibiotics is related to nephrotoxicity due to interstitial nephritis, acute tubular necrosis and intratubular crystal deposition, which leads to an impaired kidney function [ 28 ].…”
Section: Introductionmentioning
confidence: 99%